Способ получения поликристаллического кремния - Тимербулатов Т. Р. Тимур Рафкатович; Пинов А. Б. Ахсарбек Борисович; Гаврилов П. М. Петр Михайлович; Прочанкин А. П. Александр Петрович; Муравицкий С. А. Степан Александрович; Войнов О. Г. Олег Георгиевич; Болгов М. В. Михаил Викторович
опубл. 20.02.13